Effects of subsidizing the first employee – Empirical evidence from Finland - Nivala, Annika (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Small businesses form a significant share of all businesses and employ a large share of all employees. Therefore, governments are often interested in subsidizing them and especially employment in smaller firms. Nonemployer firms have received special interest, especially in Finland, due to their large share of all businesses. It has been argued that the government should encourage them to hire by subsidizing employment. However, there is no evidence on the effectiveness of such policies. In general, there is surprisingly little evidence on how small firms react to employment subsidies or of employment subsidies targeted according to firm characteristics. The subject of this thesis is the effects of subsidizing the first employee. While theoretical background suggests the subsidy might have efficiency gains, because there might be market inefficiencies that lead to too little employment in small firms. The focus of this research, however, is on the empirical evidence. There was a regional subsidy for hiring the first employee in Finland between 2007 and 2011. Nonemployer firms in the subsidy area were eligible for a wage subsidy for two years when they hired the first employee. The design of the subsidy enables studying the effects in a natural experiment framework that are nowadays popular in public economics. It can be shown that the area without the subsidy provides a good counterfactual to the area where the subsidy was available. Therefore, the effects of the subsidy can be estimated with difference-in-differences method. This method compares the change in the subsidy area to the change in the area without the subsidy. The data used is firm level data spanning from 2000 to 2013. The data is provided by the Finnish Tax Administration including tax declarations by all Finland based companies. The effects for hiring decisions are estimated by examining the effects for alternative variables such as employment, wage expenditure and turnover. According to the results, the subsidy did not have statistically significant effect on any of the variables of interest. Therefore, it can be concluded that the subsidy did not increase hires in nonemployer firms. This implies that the labour demand elasticity of nonemployer firms is very small. The results are in line with previous literature on the effectiveness of general employment subsidies in Scandinavia that suggest that labour demand elasticity is rather small resulting in small or no effects of employment subsidies. However, my research provides new evidence on labour demand of nonemployer firms especially that has not been studied before. The results are in line with the observation that most nonemployer firms are self-employed persons who are not interested in growing their business to employ others as well, but only provide for themselves. Because of this employment subsidies to the self-employed are not particularly well targeted. The theoretical grounds for the subsidy actually hold for other small firms as well, so it can be argued the subsidy would be more effective if it was extended for hiring the first few employees.